10.61533 PENGARUH KOMPETENSI SDM, SISTEM INFORMASI AKUNTANSI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN DANA BANTUAN OPERASIONAL SEKOLAH (STUDI KASUS SEKOLAH JENJANG SD DI KECAMATAN PANGKALANBARU) - Wandari, Melanda; Oktalina, Gayatria; Tri Setyo Mulyani, Hendarti (Jurnal Ilmiah Niaga Bisnis Elektronik, 2024)
This study aims to examine the effect of HR Competence, Accounting Information Systems and Internal Control Systems on the Quality of Financial Statements of School Operational Assistance Funds at the Pangkalanbaru District Elementary School level. The population in this study were elementary schools that were willing to conduct research in Pangkalanbaru District with a total sample of 13 elementary schools and a total of 37 respondents. Data collection techniques using Purposive Sampling techniques with Quantitative research methods using Questionnaires. Analysis techniques used are descriptive statistical analysis, instrument test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that HR Competence has a positive and significant effect on the Quality of BOS Fund Financial Statements, Accounting Information Systems has no effect on the Quality of BOS Fund Financial Statements, and Control Systems has a positive and significant effect on the Quality of BOS Fund Financial Statements.